The Florida Melanoma Trial I: A Prospective Multicenter Phase I/II Trial of Postoperative Hypofractionated Adjuvant Radiotherapy with Concurrent Interferon-Alfa-2b in the Treatment of Advanced Stage III Melanoma with Long-Term Toxicity Follow-Up. (19th February 2012) - Finkelstein, Steven E.; Trotti, Andy; Rao, Nikhil; Reintgen, Douglas; Cruse, Wayne; Feun, Lynn; Sondak, Vernon; Yu, Daohai; Zhu, Weiwei; Gwede, Clement; DeConti, Ronald
Abstract : Radiotherapy (RT) and interferon-alfa-2b (IFN α -2b) have individually been used for adjuvant therapy stage III melanoma with high-risk pathologic features. We hypothesized that concurrent adjuvant RT and IFN α -2b may decrease the risk of regional recurrence following surgery with acceptable toxicity. A prospective multicenter phase I/II study was conducted to evaluate hypofractionated RT with concurrent IFN. Induction IFN α -2b, 20 MU/m 2 /d, was administered IV ×5 consecutive days every week for 4 weeks. Next, RT 30 Gy in 5 fractions was given with concurrent IFN α -2b, 10 MU/m 2 SQ 3 times per week on days alternating with RT. Subsequent maintenance therapy consisted of adjuvant IFN α -2b, 10 MU/m 2 SQ 3 times per week to a total of 1 year. To fully evaluate patterns of failure, long-term follow-up was conducted for up to 10 years. A total of 29 consenting patients were enrolled between August 1997 and March 2000. The maximum (worst) grade of acute nonhematologic toxicity during concurrent RT/IFN α -2b (and up to 2 weeks post RT) was grade 3 skin toxicity noted in 2 patients (9%). Late effects were limited. Probability of regional control was 78% (95% CI: 55%–90%) at 12 months. The median follow-up (range) was 80 (51–106) months among ten survivors (43%). The median overall survival was 34.5 months while the median failure-free survival was 19.9 months. Postoperative concurrent hypofractionated RT with IFN α -2b for advanced stage III melanoma appears to be associated with acceptable toxicity and may provide reasonable in-field control in patients at high risk of regional failure.